Spiritual and Identity Transformations of Migrants: An Approach from the Experience of an Andean Community - Guerra, Castillo (Religions, 2019)
Understanding transformations in the spirituality of people involved in migration processes poses new challenges to theological approaches that usually operate within national or regional boundaries. A central question in this study is how to approach transformations in spirituality and identity, taking into account the migrants' orientations, both towards their country of origin and towards their country (or countries) of destination. This articles argues that migration is an experience that leads to profound changes in the spirituality and identity of migrants. Taking advantage of insights from transnational studies, this article investigates the traits of a spirituality transformed from a transnational identity with regard to the experience of an Andean community. Particularly, their devotion to the Lord of Qoyllor Rití in Curzco, Lima and New York.